Effect of antioxidant-rich propolis and bee pollen extracts against D-glucose induced Type 2 Diabetes in rats - Hassan Laaroussi (2020)
The present study was designed to investigate the preventive effect of propolis, bee pollen and their combination on Type 2 diabetes induced by D-glucose in rats. The study was carried out by feeding daily two concentrations (100 and 200 mg/Kg BW) of propolis or bee pollen (or their combination to normal (non-diabetic) and diabetic rats for a period of 16 weeks. In vivo biochemical changes associated to diabetes are induced by drinking a solution containing 10% of D-glucose (diabetic rats). The in vitro antioxidant activity was also evaluated and the chemical composition of propolis and bee pollen extracts was determined by UHPLC-DAD. Phytochemical composition of propolis and bee pollen revealed the presence of several natural antioxidants, such as hydroxycinnamic acids, hydroxybenzoic acids, flavonoids, flavan-3-ols and stilbens. The major antioxidant compound present in propolis was Naringin (290.19±0.2 mg/Kg) and in bee pollen was apigenin (162.85±17.7 mg/Kg). These results have been related with a high antioxidant activity, more intense in propolis extract. In rats, the administration of D-glucose had induced hyperglycemia (13.2 ± 0.82 mmol/L), increased plasmatic insulin levels (25.10 ± 2.12 U/L) and HOMA-IR index (14.72 ± 0.85) accompanied with dyslipidemia, elevation of hepatic enzyme levels, and a change in both serum renal biomarkers and plasmatic calcium. The co-administration of propolis and bee pollen extracts alone or in combination restored these biochemical parameters and attenuated the deleterious effects of D-glucose on liver and kidney functions. Furthermore, these effects were better attenuated in the combined therapy-prevented diabetic rats. Hence, it is possible to conclude that propolis and bee pollen can be used as a preventive natural product against diabetes induced dyslipidemia and hepato-renal damage.